2000
DOI: 10.1007/s003600000099
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of fatty acids from female seal blubber via milk to pup blubber

Abstract: Fatty acids were determined by gas chromatography followed by principal component analysis (PCA) and soft independent modelling of class analogy (SIMCA) in the blubber of 18 female grey seals, Halichoerus grypus, in their milk and in the blubber of their 1-week-old nursing pups. Large individual differences were observed in both blubber and milk content of fatty acids. The fatty acid composition of the milk was systematically different from the composition in maternal blubber, with higher relative amounts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The remaining seals were identified as having a mixed diet of fish and squid. This methodology assumes that there is little modification of the FA concentrations from prey to predator (Grahl-Nielsen & Mjaavatten 1991; Iverson 1993; Grahl-Nielsen et al 2000). The summary of these classifications is presented relative to season and geographical foraging region in table 3.…”
Section: Icichthys Australis Gymnoscopelus Bolini G Fraseri G Nimentioning
confidence: 99%
“…The remaining seals were identified as having a mixed diet of fish and squid. This methodology assumes that there is little modification of the FA concentrations from prey to predator (Grahl-Nielsen & Mjaavatten 1991; Iverson 1993; Grahl-Nielsen et al 2000). The summary of these classifications is presented relative to season and geographical foraging region in table 3.…”
Section: Icichthys Australis Gymnoscopelus Bolini G Fraseri G Nimentioning
confidence: 99%
“…This may be due to the females' blubber stores being dramatically depleted during the nursing period from mid-June to mid-July. During the short, intense lactation period in phocid seals, lipid metabolism is intensified and the FA composition of the blubber changes as a consequence of a selective utilization of particular depot FAs (Iverson et al 1995;Grahl-Nielsen et al 2000). Depot fats of adult males would not be as dramatically affected by the reproductive period as those of females.…”
Section: Adult Malesmentioning
confidence: 99%
“…John and Lund 1996;Iverson et al 1997aIverson et al , 2004. Although the presence of some FAs is directly traceable to a specific source, the universality of the use of FAs as dietary tracers is a point of some contention in the recent scientific literature (e.g., Viga and Grahl-Nielsen 1990;Grahl-Nielsen and Mjaavatten 1991;Hove and Grahl-Nielsen 1991;Smith et al 1997Smith et al , 1999Grahl-Nielsen 1999;Grahl-Nielsen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on nurs-ing hooded seals Cystophora cristata, it was found that the blubber of pups attained an FA composition almost identical to that of the milk (Iverson et al 1995a). However, in a study conducted on nursing grey seals Halichoerus grypus, it was found that the blubber of pups had a closer resemblance to the mother's blubber than to the milk (Grahl-Nielsen et al 2000). In another study, the relative amounts of FAs in the blubber of nursing grey seal pups were found to be between one-third and one and a half times that of the relative amounts of the FA in the milk (Iverson et al 2004).…”
Section: Introductionmentioning
confidence: 97%